(untitled) (REMUNOM, 2024)
Violence against women is a public health issue that affects thousands of women in Brazil, despite the advancements promoted by the Maria da Penha Law. The main objective of the study is to better understand this context of violence against women in the municipality of Teófilo Otoni-MG, as it leaves traces of violence, inequality, and poverty in the Vale do Mucuri region. Regarding its approach, the research is classified as qualitative, characterized as descriptive in its aims and documentary in its methods. The results indicate that violence against women in Teófilo Otoni-MG is a cultural reflection of a society still permeated by machismo and patriarchy, manifesting in various forms that devalue and oppress women. This reality is exacerbated by the conditions of poverty, inequality, and violence that characterize the city. Additionally, society also bears responsibility, reflected in the lack of information, support, autonomy, security, access to justice, and specialized services for women victims of violence. It is crucial for a joint effort of civil society, public agencies, and institutions to develop and implement comprehensive strategies to combat domestic violence, aiming to protect and empower women in Teófilo Otoni-MG and across the country.